Mr. Meredith and the truly remarkable stone - Chetwin, Grace (New York : Collier Macmillan, 1989)
When Mr. Meredith finds a remarkable stone, he builds a series of ever grander structures in which to house it.
Keywords: Rocks--Fiction.; Children stories